KORELASI PERSEPSI PELANGGAN DAN KUALITAS PELAYANAN DENGAN KEPUASAN PELANGGAN TRANSPORTASI ONLINE GRAB BIKE DI KOTA PALEMBANG - Debby Marthalia; Syaryoni Naidu Komaria (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2019)
The correlation Between Customer's Satisfactionand Service Quality with Satisfaction of Online Transportation Grab Bike Customers in Palembang. The Research of Fledgling Lecturer. This research aims to know the relation of customer's perception and service quality with customer's satisfaction. Hypothesis of this research : (1) There was a relation of customer's perception and service quality with customer's satisfaction. (2) There was a relation between customer's perception and satisfaction, (3) There was a relation between service quality and customer's satisfaction. It took place in Palembang city with all 100 customers as respondents. The instrument which used was poll concerned about customer's perception and service quality as being the independent variable and another poll was related to customer's satisfaction as the dependent one. The istrument was validated by correlation formula, Pearson Product Momen (PPM). Mean while, its reliability was measured by alpha cronbach. The data analysis used multiple regression analysis. According to the result of this research, it was discovered that : (1) There was a relation between independent variable and dependent variable in which the amount of multiple correlation coefficient (R) was 0,929, (2) Dependant Variable was stated by independent variable that contributed 86,3%, (3) There was a relation between customer's perception and satisfaction as well as service quality and customer's satisfaction, somehow, there was a significant rapport between customer's perception and service quality with the customer’s satisfaction of online transportation Grab Bike in Palembang city at once.